2002
DOI: 10.1007/s001980200108
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Corticosteroid-Induced Osteoporosis: a Meta-analysis

Abstract: Abstract. Studies of oral corticosteroid dose and loss of bone mineral density have reported inconsistent results. In this meta-analysis, we used information from 66 papers on bone density and 23 papers on fractures to examine the effects of oral corticosteroids on bone mineral density and risk of fracture. Strong correlations were found between cumulative dose and loss of bone mineral density and between daily dose and risk of fracture. The risk of fracture was found to increase rapidly after the start of ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
280
3
16

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,038 publications
(313 citation statements)
references
References 104 publications
14
280
3
16
Order By: Relevance
“…Certainly, GC-induced osteoporosis is a well-known adverse consequence of chronic GC therapy, and several groups have reported that daily prednisone doses as little as 10 mg or lower result in clinically significant bone loss (16,32). In the present investigation, circulating concentrations of the bone formation marker osteocalcin decreased dramatically within hours of administration of all prednisone doses and remained suppressed for at least 24 h. Of the bone formation markers analysed, osteocalcin was the most sensitive to GC treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certainly, GC-induced osteoporosis is a well-known adverse consequence of chronic GC therapy, and several groups have reported that daily prednisone doses as little as 10 mg or lower result in clinically significant bone loss (16,32). In the present investigation, circulating concentrations of the bone formation marker osteocalcin decreased dramatically within hours of administration of all prednisone doses and remained suppressed for at least 24 h. Of the bone formation markers analysed, osteocalcin was the most sensitive to GC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…GCs reduce osteoblast function and replication as well as increase osteoblast apoptosis (1,8,9,10). Although the specific mechanism by which GCs interfere with osteoblast function remains unclear, reductions in bone formation markers have been reported to occur within days of treatment with prednisone (11,12,13,14,15), and increases of about two-or three-fold in the relative risk of hip and vertebral fractures in patients receiving GCs have been reported (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…(3) However, lack of bone formation and function of OB lineage cells cannot be responsible alone for some of the most important effects that GCs have on bone. These include rapid increase in fracture risk within the first 3 to 6 months of treatment, (2,4) which could be explained best by an effect of GCs on bone resorption itself. In addition, bone-resorption markers increase immediately in patients receiving intravenous GCs, and the maximum increase in serum cross-linked C-telopeptide (CTX) was already reached 24 hours after the very first infusion.…”
Section: Introductionmentioning
confidence: 99%
“…Одним из осложне-ний терапии ГК является потеря костной массы и сопутст-вующие этому переломы [9]. Переломы костей скелета имеют различную локализацию, однако наиболее высокий риск отмечался для переломов позвонков, которые, как правило, протекают бессимптомно [10].…”
Section: Review Of American College Of Rheumatology (Acr) Clinical Guunclassified